COMMUNITY ENGAGEMENT FOR DEVELOPMENT: GEN Z AS THE AGENT OF INNOVATION TO ACHIEVE SDGs - Deatri Arumsari Agung; Monica Adjeng Erwita; Dirgantara Dahana Mokoginta; Gesti Memarista; Aldo Hardi Sancoko; Andy Pratama Sulistyo; Natalia Kristina; Alpi Mawasti; Visi Saujaningati Kristyanto (LPPM, Universitas Katolik Widya Mandala Surabaya, 2022)
The pandemic era has caused a loss of opportunities to obtain information regarding product management through online media. This led to the implementation of this community service activity which aims to help the MSME community in Surabaya to innovate by using online platforms to increase product sales. The Abdimas team of lecturers from the Faculty of Business and the Faculty of Entrepreneurship at UKWMS is also assisted by UKWMS students and international students who are included in generation Z, there is also the provision of international materials by lecturers from TAR UMT Malaysia who support community service activities with continuous innovation to help MSME businesses with social media. The series of activities were carried out using the service-learning method in two sub-themes namely product improvement and social media management for 5 days. The results of community service activities are prototype updates on the packaging, product design, and changes to MSME owners' social media which can later be included in local village bazaar activities and outlets at culinary tourism centers in Surabaya. In addition, students also get many benefits to apply the knowledge gained in class.